The Effect of Earnings Management, Capital Intensity, Firm Size, Fiscal Loss Compensation on Tax Avoidance: Pengaruh Manajemen Laba, Capital Intensity, Ukuran Perusahaan,Kompensasi Rugi Fiskal Terhadap Penghindaran Pajak - Nisa, Khoirun; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2022)
Effect of Earnings Management, Capital Intensity, Firm Size, and Fiscal Loss Compensation on Tax Avoidance (Study on Food and Beverage Companies listed on the Indonesia Stock Exchange in 2015-2019). This study aims to obtain evidence on the effect of earnings management, firm size, capital intensity, and compensation for tax losses on tax avoidance. In this study, using purposive sampling method to show the sample. The population in this thesis are manufacturing companies with the food and beverage sector with a population of 80 companies listed on the Indonesia Stock Exchange (IDX). With the selection of criteria, there is a total sample of 16 companies in an observation period of 5 years starting from 2015-2019. In this observation, tax avoidance is calculated through the formulation of the ETR. The tester for the hypothesis in this observation uses multiple regression analysis techniques. The results of this observation show that earnings management, firm size, and tax loss compensation affect tax avoidance. But capital intensity can not affect tax avoidance.